Janapadodhwamsa: An Ayurvedic Preventive Model For Contemporary Environmental And Public Health Challenges. - Sharma , Sagar; Kaithwas , Swapnil (Journal of Neonatal Surgery, 2025)
Ayurveda, the traditional medical system of India, offers a comprehensive and preventative approach to health that encompasses individual, social, and environmental well-being. Classical Ayurvedic texts stress the health of whole populations and call large-scale health problems **Janapadodhwamsa**, which means that societies are sick because of shared environmental and moral factors. This paper is attempted to study and analyse Janapadodhwamsa as an Ayurvedic preventive framework for addressing contemporary environmental and public health challenges. Ayurvedic texts like the Charaka Samhita, Sushruta Samhita, Bhela Samhita, and Kashyapa Samhita, as well as recent scientific studies on public health, epidemics, and environmental health were studied. Adharma, which comes from Prajnaparadha, is what mostly causes Janapadodhwamsa. Along with this the air (Vayu), water (Jala), land (Desha), and seasonal cycles (Kala) dushti results in environmental diseases, leading to extensive disease outbreaks. The concept of Janapadodhwamsa is discussed in perspective of modern public health problems such pandemics, illnesses caused by pollution, climate change, urbanisation, and lifestyle disorders. Ayurvedic preventive strategies explained in swasthvritta like Dinacharya, Ritucharya, Sadvritta, Panchakarma, Rasayana, dhupana karma etc along with chikitsa explained in Janapadodhwamsa is discussed..